Meal replacement by formula diet reduces weight more than a lifestyle intervention alone in patients with overweight or obesity and accompanied cardiovascular risk factors—the ACOORH trial - Halle, Martin; Roehling, Martin; Banzer, Winfried; Braumann, Klaus Michael; Kempf, Kerstin; Mccarthy, David; Schaller, Nina; Predel, Hans Georg; Scholze, Jurgen; Fuhrer-Sakel, Dagmar; Toplak, Hermann; Berg, Aloys; et al. (European Journal of Clinical Nutrition, 2021)
Background: As formula diets have demonstrated to be effective in reducing weight, we hypothesised that in patients with overweight or obesity and accompanied cardiovascular risk factors, combining a liquid formula diet with a lifestyle intervention is superior in reducing weight and improving cardiovascular risk factors than lifestyle intervention alone. Methods: In this multicenter RCT 463 participants with overweight or obesity (BMI: 27–35 kg/m²; at least one additional co-morbidity of the metabolic syndrome) were randomised (1:2) into either a control group with lifestyle intervention only (CON, n = 155) or a lifestyle intervention group including a liquid meal replacement (INT, n = 308). Both groups used telemonitoring devices (scales and pedometers), received information on healthy diet and were instructed to increase physical activity. Telemonitoring devices automatically transferred data into a personalised online portal and acquired data were discussed. INT obtained a liquid meal replacement substituting three meals/day ( 1200 kcal) within the first week. During weeks 2–4, participants replaced two meals/day and during weeks 5–26 only one meal/day was substituted (1300–1500 kcal/day). Follow-up was conducted after 52 weeks. Intention-to-treat analyses were performed. Primary outcome was weight change. Secondary outcomes comprised changes in cardiometabolic risk factors including body composition and laboratory parameters. Results: From the starting cohort 360 (78%, INT: n = 244; CON: n = 116) and 317 (68%, INT: n = 216; CON: n = 101) participants completed the 26-weeks intervention phase and the 52-weeks follow-up. The estimated treatment difference (ETD) between both groups was −3.2 kg [−4.0; −2.5] (P < 0.001) after 12 weeks and −1.8 kg [−2.8; −0.8] (P < 0.001) after 52 weeks. Conclusions: A low-intensity lifestyle intervention combined with a liquid meal replacement is superior regarding weight reduction and improvement of cardiovascular risk factors than lifestyle intervention alone.
CRIS-Team Scopus Importer:2023-03-08